Interactive Didactic Strategies based on Learning Through Collaboration and Cooperation - BARBU, Florentina Irina (Journal of Research in Educational Sciences; Vol 1 No 1 (2010): JRES Volume I Issue 1(1) Summer 2010, 2010)
The didactic strategy is the efficient way through which the schoolmaster / teacher helps his pupils to reach knowledge and develop the intellectual capacities, the skills, the habits, the faculties, the feelings and the emotions. It is made of a complex and circular structure of methods, techniques, ways of teaching and patterns of activity organization, complementary, in base of which the headmaster / teacher elaborates a plan of working with the pupils, in order to efficiently accomplish their learning. Using the interactive methods promotes learning by cooperation as a superior form of psycho-social interaction, based on mutual support, on the constant effort of all the pupils.